CONTRIBUTION OF ISLAMIC CIVILISATION TO SCIENCE EDUCATION AND TECHNOLOGY : SOME FRESH INSIGHTS - Rafiabadi, Hamid Naseem (Universitas Islam Indonesia, 2017)
This article underlines the epistemological miss-conception of knowledge in Islam which has been offered by many Muslim scholars. Muslim scholars tend to divide knowledge into fardl al-kifayah and fardl ‘ain. This miss-conception could lead into secular paradigm where there are Islamic science and non-Islamic science. On the contrary, Islam actually has given comprehensive guide to all aspects of life. Islam did not classify knowledge to thus classification nor to sacred and mundane knowledge. However, some Islamologists, especially Western ones, like to state that Islam has nothing to do with science, especially natural ones. Hence, this article concentrates particularly on technology in Islam. These issues are discussed especially based on perspectives of Said Nursi, Ismail Raji al Faruqi, and Sir Syed and Maududi. As results, this article proves that Islam has done more than Christianity to science. Furthermore, the development of technologies in the West nowadays was originally founded by Islam. Unfortunately, because of the secular ideology, Moslems have forgotten those historical-scientific facts. This brings people to separate religious values such as ethics from natural sciences. Therefore, this article finally invites Moslems to think of integrative approach since the aim of Islamic education is to produce an integrated and perfect individual, insān kāmil.Keywords: Islamization, Secularism, Orientalism, Islamic education, Islamic science, History of science.